Analysis of Mathematical Problem Solving Ability Viewed from Gender Differences in Public High Schools - Sely Jera Umaratu; Anggriati Ledu Ngaba; Mayun Erawati Nggaba (JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to analyze students' mathematical problem solving abilities in terms of gender differences and describe the obstacles in solving problems in the form of linear programming story questions. This type of research is descriptive with a qualitative approach. The research subjects were 18 students of class XI MIA 2 SMA Negeri 1 Kambera including 9 male students and 9 female students and the supporting subjects were compulsory mathematics teachers and specialization mathematics teachers. The results of the study using the Polya indicator in terms of gender differences showed the overall average score obtained by female students with a score of 49.07 was superior to male students who scored 42.37. This shows that there are gender differences in solving a problem due to lack of understanding of the problem in question, not working carefully, rarely practicing questions.